Assessment of senile asthenia syndrome using the Frailty and Edmonton frail scales in elderly and senile patients who underwent emergency abdominal surgery - Danyliuk, M. B.; Zavhorodnii, S. M.; Yareshko, N. O.; Bachurin, A. V. (Modern medical technology, 2023)
The aim of the work was to compare the effectiveness of the assessment of senile asthenia syndrome using the Frailty and Edmonton Frail scales in elderly and senile patients undergoing emergency abdominal surgery. Materials and methods. The study included 80 patients aged 60 to 89 years with a diagnosis of acute calculous cholecystitis. A correlation was determined between asthenia and the severity of the patient’s condition according to the P-POSSUM scale, the peak value of the increase in the risk of postoperative complications and mortality occurs in patients with a sum of points >32, p = 0.012. The syndrome of senile asthenia using the Edmonton Frail scale was detected in 30 (37.5 %) patients, according to the Frailty scale – 32 (40.0 %), U = 3120.0, p = 0.7862. Results. The main advantage of the Edmonton Frail scale is the examination time of 22 ± 3 min, while with the Frailty scale 360 ± 22 min (U = 24.5, p < 0.0001). Based on the assessment of the severity of the condition using the P-POSSUM scale, we determined a direct correlation of average strength between the presence of asthenia and the number of points: Edmonton Frail subgroup A – rs = 0.81, p = 0.000001. The same results, respectively, on the Frailty scale – rs = 0.78, p = 0.000004. The frequency of complications increases significantly in the category of patients with asthenia, which is confirmed by both the Edmonton Frail scale – 23.3 % (U = 605.0, p = 0.0087), and the Frailty scale – 21.9 % (U = 632.0, p = 0.0150). Conclusions. The frequency of detection of senile asthenia syndrome using the Edmonton Frail and Frailty scale in patients was equivalent (U = 3120.0, p = 0.7862). The Edmonton Frail scale is more convenient to use in urgent situations, and the mean time to diagnose asthenia using it was 22 ± 3 min, while the complete diagnosis using the Frailty scale took 360 ± 22 min (U = 24.5, p < 0.0001). A significant increase in the frequency of postoperative complications was determined in the category of patients with asthenia, confirmed both by the Edmonton Frail scale – 23.3 % (U = 605.0, p = 0.0087), and by the Frailty scale – 21.9 % (U = 632.0, p = 0.0150).